The Role of Operational Audit in Supporting Sales Effectiveness (Study PT. Pacific Indo Packing) - Ahmad Wawanda Iswanto; Anjar Sulistyowati; Ali Muhajir (Basic and Applied Accounting Research Journal, 2023)
This study aims to determine how big the role of operational audit in supporting the effectiveness of sales in the company pt. pacific indo packing. because it is quite important to know how the role of operational audit and sales effectiveness in the company is whether the sales that have been carried out by the company have been effective or vice versa. In this study, the researcher used a quantitative descriptive method. The research method is intended to collect data according to the actual situation and provide an overview and analysis of the existing problems so that it can provide a fairly clear picture of the object under study. The sample in this study is the finance / sales department and the financial statements of the budget and sales realization in 2018 - 2020. The technique of analyzing the percentage results using the provisions, Less than or equal to 70% (≤ 70%) means that the sales function audit does not play a role in supporting sales effective. More than 70% (>70%) means that the sales function audit plays a role in supporting effective sales. Based on the analysis and the results of the questionnaire, the percentage of operational audit participation is 94.48%, this can be seen from the calculation of the answers to the questionnaire using existing benchmarks. So from the results of the percentage can be concluded that the role of operational audit at PT. PACIFIC INDO PACKING Lamongan can be said to play a role because the results of the operational audit presentation are 94.48% while the benchmark can be said to play a role if it is more than 70%.